2005
DOI: 10.1111/j.1745-7254.2005.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2 celecoxib derivatives: analgesic effect and selectivity to cyclooxygenase-2/11

Abstract: Aim: To evaluate the analgesic effects of 2 celecoxib derivatives and their inhibitory effects on cyclooxygenase (COX). Methods: Four antinociceptive assays were used: the acetic acid-induced writhing test, hot plate test, hot tail-flick test and formalin test. Three doses were used in the analgesic assays and ED 50 values were calculated. For the selectivity assay, macrophages were incubated with test compounds at various concentrations and then stimulated with calcimycin or lipopolysaccharide (LPS). The amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
4
14
0
Order By: Relevance
“…The study indicated that IT celecoxib had antinociceptive activity in late phase of formalin test in a dose-dependent manner. These data are in agreement with other studies in which IT celecoxib administration could inhibit nociception in both phases of formalin test (26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…The study indicated that IT celecoxib had antinociceptive activity in late phase of formalin test in a dose-dependent manner. These data are in agreement with other studies in which IT celecoxib administration could inhibit nociception in both phases of formalin test (26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, reference drug PC407 exhibited 100% inhibition of COX-2 isoform, without any inhibition of COX-1 isoform at 0.1 lM concentration, which was consistent with the known facts. 4,11 As expected, prodrug 3b showed relatively less potency in COX-2 inhibition in vitro than PC407 due to the block of sulfonamide, which is the main pharmacophore group in PC407. 11 In vivo pharmacological evaluation of the water soluble prodrug 3b was carried out to assess their potential analgesic activity in the acetic acid-induced writhing assay.…”
Section: Introductionmentioning
confidence: 77%
“…4,11 As expected, prodrug 3b showed relatively less potency in COX-2 inhibition in vitro than PC407 due to the block of sulfonamide, which is the main pharmacophore group in PC407. 11 In vivo pharmacological evaluation of the water soluble prodrug 3b was carried out to assess their potential analgesic activity in the acetic acid-induced writhing assay. [20][21][22] The writhing test is a nociceptive model characterized by repeated contractions of the abdominal muscles.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations